Koi Fish Cultivator Marketing Strategy During The Pandemic In Ciseeng, Bogor Regency - Sa'diyah, Sholikatus; Rifai, Agus; Subchi, Imam (International Journal of Educational Research & Social Sciences, 2022)
The Covid-19 pandemic has had an impact on various sectors in Indonesia. One of the sectors affected is koi fish farming in Ciseeng, Bogor Regency. This study focuses on the strategies used by ornamental koi fish cultivators in Ciseeng, Bogor Regency during the Covid-19 pandemic. The research methodology used by the researcher is a qualitative method with a three-month fieldstudy from August to October 2021. By using participatory observation and in-depth interviews as data collection methods, plus purposive sampling method as a subject determination. The results of this study are; During the pandemic, koi fish farmers in Cibogo Village, Ciseeng, Bogor Regency do side jobs to maintain and increase income. The side jobs carried out by the cultivators include being construction workers, as well as other fish farming. During the pandemic, only one farmer tried to market online, while the other 14 did traditional marketing. This is because the cultivators do not receive marketing strategy training or assistance from the local government